2021
DOI: 10.1056/nejmoa2114583
|View full text |Cite
|
Sign up to set email alerts
|

Waning Immune Humoral Response to BNT162b2 Covid-19 Vaccine over 6 Months

Abstract: Background Despite high vaccine coverage and effectiveness, the incidence of symptomatic infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been increasing in Israel. Whether the increasing incidence of infection is due to waning immunity after the receipt of two doses of the BNT162b2 vaccine is unclear. Methods We conducted a 6-month longitudinal prospective study involving vaccinated health care workers who were tested monthly for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

218
1,272
26
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,567 publications
(1,649 citation statements)
references
References 25 publications
218
1,272
26
15
Order By: Relevance
“…There seemed no difference between cellular immunity conferred by natural infection and the reduction in cellular immunity by vaccines. It has been previously reported that the antibody titer is negatively correlated with age up to 6 months after vaccination [9], but SP-specific T-cell response has not been related to age [10]. In our study, there was no correlation among age, gender, BMI, alcohol, or smoking.…”
Section: Discussioncontrasting
confidence: 65%
“…There seemed no difference between cellular immunity conferred by natural infection and the reduction in cellular immunity by vaccines. It has been previously reported that the antibody titer is negatively correlated with age up to 6 months after vaccination [9], but SP-specific T-cell response has not been related to age [10]. In our study, there was no correlation among age, gender, BMI, alcohol, or smoking.…”
Section: Discussioncontrasting
confidence: 65%
“…Although the scale of case number in Y axis in supplementary figure 7 As far as the results of external prediction are concerned, there were three weeks between 9 August and 29 August 2020 in which the observed numbers of domestic cases were beyond the upper limit of surveillance level. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) Southern (42), Waitematā (38), Auckland (34), Canterbury (34), Waikato (26)…”
Section: External Validation Of the Epidemic Surveillance Model For Importation Casesmentioning
confidence: 99%
“… 8 Other reports from Israel and Qatar indicate speedily declining protection. 2 , 3 Although these reports strengthen the case for a booster dose of BNT162b2, there is no evidence yet to suggest that global policies related to other vaccines should be influenced by this experience.…”
mentioning
confidence: 96%
“…Currently approved vaccines provide high levels of protection against serious illness, but do not confer mucosal immunity to resist entry of the virus into the respiratory tract. When mostly mild breakthrough infections were reported from different countries, 1 , 2 , 3 concern arose that individuals with a fast fading immune response to the standard vaccination schedule might experience serious illness if infected. 1…”
mentioning
confidence: 99%